Relación entre la composición corporal y niveles actividad física en adultos con sobrepeso y obesidad en la asociación de mujeres emprendedoras de Vinces – Los Ríos, mayo –septiembre 2019. - Rendón García, Franklin Ronaldo (2019)
The present investigation will be analyzed in the Association of Women Entrepreneurs of the city of Vinces, in which the observations of how to lead their lifestyles will then be made; These presented problems associated with obesity and overweight, as well as inactivity. The essential objective of this study was to determine the body composition and levels of physical activity in adults with overweight and obesity in the association of women entrepreneurs from Vinces - Los Ríos, May - September 2019. For this purpose a descriptive methodology was used, using The analytical and synthetic methods also applied the IPAQ: short self-administered format of the last 7 days to be used in which the information on physical activity was collected. For the variable body composition, as well as overweight and obesity, anthropometric measurements were used. Among the main findings we were able to determine that physical inactivity has a close relationship between body composition and overweight and obesity, thus being the body mass index sheds 81% overweight and 13% obesity type 1 and 6 % of type 2 obesity; In the other component, such as the percentage of fat, it is determined that 85% of them have a high level of fat, which is reflected by studies. And 15% of the 52 respondents have a very high level of fat and even problems associated with cholesterol according to the dialogue with them. In this sense at the time of determining their muscular condition, 88% of having a normal muscular condition was determined being the rest of the percentage of fat; while others were constituted by a higher level of fat and less muscles; the population being 12% of all respondents. Therefore, it is important to emphasize that it is necessary for people to maintain a constant physical activity for the benefit of our health.